Perspective on BVDV control programs. (8th June 2015) - Givens, M. Daniel; Newcomer, Benjamin W.
Abstract Programs for control and eradication of bovine viral diarrhea virus (BVDV) are often considered prudent when the expense of a control program within a specified time frame effectively prevents loss due to disease and the expense of control does not exceed the costs associated with infection. In some geographic areas, concerns about animal welfare or desires to reduce antibiotic usage may motivate BVDV control even when control programs are associated with a lack of financial return on investment. In other geographic areas, concerns about financial return on investment may be the key motivating factor in considering implementation of BVDV control programs. Past experiences indicate that systematic, well-coordinated control programs have a clear potential for success, while voluntary control programs in cultures of distributed decision-making often result in notable initial progress that ultimately ends in dissolution of efforts. Segmentation of the cattle industry into cow–calf producers, stocker/backgrounders, and feedlot operators amplifies the distribution of decision-making regarding control programs and may result in control measures for one industry segment that are associated with significant costs and limited rewards. Though the host range of BVDV extends well beyond cattle, multiple eradication programs that focus only on testing and removal of persistently infected (PI) cattle have proven to be effective in various countries. While some individuals consider education of producers to be sufficient to stimulate eradication of BVDV, research surrounding the adoption of innovative health care procedures suggests that the process of adopting BVDV control programs has a social element. Collegial interactions and discussions may be crucial in facilitating the systematic implementation necessary to optimize the long-term success of control programs. Compulsory control programs may be considered efficient and effective in some regions; however, in a nation where individual identification of cattle remains voluntary, the likelihood of effective compulsion to control BVDV within a farm or ranch appears to be very unlikely. While currently available diagnostic tests are sufficient to support BVDV eradication via systematic, well-coordinated programs, the development of a diagnostic procedure to safely and consistently detect the gestation of a PI fetus after 5 months of gestation would be a valuable research breakthrough. This desired testing modality would allow diagnosis of PI calves, while the dam continues to provide biocontainment of the infected fetus. This development could speed the progress of control programs in achieving the goal of BVDV control and eventual eradication.